Treatment of urinary tract infections in condition of growing antibiotic resistance: Antimicrobial Stewardship program - Chub, O.I.; Bilchenko, O.V.; Godlevska, O.M.; Teslenko, S.V. (Ukrainian Journal of Nephrology and Dialysis, 2019)
Resistance to common groups of antibiotics has been increasing in the treatment of urinary tract infections worldwide. In the United States, CDC has estimated that more thаn 2 million infections and 23,000 deaths are due to antibiotic resistance each year. In Europe, an еstimated 25,000 deaths are attributable to antibiotic-rеsistant infections. By 2050, it is estimated that antibiotic resistance will cause 10 million deaths every year.At the EU/EEA level, more than half (58.2%) of the E. coli isolates reported to EARS-Net for 2017 were resistant to at least one of the antimicrobial groups under regular surveillance, i.e. aminopenicillins, fluoroquinolones, third-generation cephalosporins, aminoglycosides and carbapenems. A majority (87.4%) of the third-generation cephalosporin-resistant E. coli isolates from 2017 were extended-spectrum beta-lactamase (ESBL)-positive. Use of broad-spectrum antimicrobials is a known risk factor for colonization and spread of resistant Enterobacteriaceae, including E. coli. The high levels of ESBLs and increasing resistance to key antimicrobial groups might also lead to an increased consumption of carbapenems, which in turn can increase the selection pressure and facilitated the spread of carbapenem-resistant Enterobacteriaceae. According to annual reports of CDC, WHO, EARS-Net and others,estimate that 30 percent of all antibiotics prescribed in outpatient clinics and 40 percent of all antibiotics prescribed in inpatient clinics were unnecessary. Improving the way we use antibiotics, often referred to as «antibiotic stewardship», is part of the National Action Plan. Appropriate antibiotic use means using the right antibiotic, at theright dose, for the right duration, and at the right time. The article reflects the recommendations of the European Association of Urology 2019 on the management and treatment of urinary tract infections in accordance with the principles of Antimicrobial Stewardship Program.